2009
DOI: 10.1086/597266
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pollen Load and Donor Diversity on Seed and Fruit Mass in the Columnar Cactus, Pachycereus schottii (Cactaceae)

Abstract: As seed and fruit size can influence the success of later life history stages, it is important to understand their sources of variation. In this study, we examined the effects of pollen load and donor diversity on variation in seed and fruit mass of outcrossing senita cacti {Pachycereus schottii) in the Sonoran Desert. By massing all individual seeds per fruit from pollen supplementation and donor diversity experiments, we were able to examine their effects on seed and fruit mass, compared with intra-and inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 66 publications
1
7
0
Order By: Relevance
“…In addition, the results of the current study do agree with previous reports from other taxa e.g. Hydrophyllum appendiculatum (Wolfe, 1995), Lesquerella fendleri (Mitchell, 1997) and Mirabilis jalapa (Niesenbaum, 1999;Davis, 2004), and Pachycereus schottii (Holland et al, 2009), which have shown that pollen donor diversity did not affect on seed and fruit set nor on later components of life history. In contrast, the pollen donor diversity in Rhamnus alpinus has been reported to affect on different reproductive components of F 1 progeny e.g.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, the results of the current study do agree with previous reports from other taxa e.g. Hydrophyllum appendiculatum (Wolfe, 1995), Lesquerella fendleri (Mitchell, 1997) and Mirabilis jalapa (Niesenbaum, 1999;Davis, 2004), and Pachycereus schottii (Holland et al, 2009), which have shown that pollen donor diversity did not affect on seed and fruit set nor on later components of life history. In contrast, the pollen donor diversity in Rhamnus alpinus has been reported to affect on different reproductive components of F 1 progeny e.g.…”
Section: Resultssupporting
confidence: 92%
“…Lloyd, 1980;Bernasconi 2003;Obeso, 2004;Halpern 2005;Raghavan, 2005;Gehring and Delph, 2006;Bayer et al, 2009;Holland et al, 2009;Diggle et al, 2010). These studies indicated that the levels of offspring performance in plants are mainly controlled by maternal parent, while the impact of paternal parent on the progeny performance has been less investigated (Holland et al, 2009). Therefore, it is important to understand the effects of pollen donor diversity on progeny performance in plants (Leishman et al, 2000;Westoby et al, 2002;Beaulieu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with this hypothesis is the fact that many studies have found maternal effects on seed size (Roach & Wulff 1987;Mousseau & Fox 1998;Galloway et al 2009;Holland et al 2009), and only rarely have paternal effects been observed (e.g. Marshall & Whittaker 1989;Andersson 1990).…”
Section: Introductionmentioning
confidence: 65%
“…The negative impacts of mixed pollination in this study (significant between the two hand-pollination treatments for fruit mass and seed number in S. repandus) are likely to be due to direct pollen interference from the other species when pollen is limiting. Holland et al (2009) found that pollen load accounted for less than 6% of the variation in seed and fruit mass of Pachycereus schottii.…”
Section: Effect Of Mixed Pollen Load On the Two Cactus Speciesmentioning
confidence: 96%